Coordinating resources for prospective medication risk management of older home care clients in primary care: procedure development and RCT study design for demonstrating its effectiveness - Terhi Toivo; Maarit Dimitrow; Juha Puustinen; Eeva Savela; Katariina Pelkonen; Valtteri Kiuru; Tuula Suominen; Sirkka Kinnunen; Mira Uunimäki; Saija Leikola; Marja Airaksinen (BIOMED CENTRAL LTD, 2022)
Background: The magnitude of safety risks related to medications of the older adults has been evidenced by numerous studies, but less is known of how to manage and prevent these risks in different health care settings. The aim of this study was to coordinate resources for prospective medication risk management of home care clients >= 65 years in primary care and to develop a study design for demonstrating effectiveness of the procedure.
Methods: Health care units involved in the study are from primary care in Lohja, Southern Finland: home care (191 consented clients), the public healthcare center, and a private community pharmacy. System based risk management theory and action research method was applied to construct the collaborative procedure utilizing each profession's existing resources in medication risk management of older home care clients. An inventory of clinical measures in usual clinical practice and systematic review of rigorous study designs was utilized in effectiveness study design.
Discussion: The new coordinated medication management model (CoMM) has the following 5 stages: 1) practical nurses are trained to identify clinically significant drug-related problems (DRPs) during home visits and report those to the clinical pharmacist. Clinical pharmacist prepares the cases for 2) an interprofessional triage meeting (50-70 cases/meeting of 2 h) where decisions are made on further action, e.g., more detailed medication reviews, 3) community pharmacists conduct necessary medication reviews and each patients' physician makes final decisions on medication changes needed. The final stages concern 4) implementation and 5) follow-up of medication changes. Randomized controlled trial (RCT) was developed to demonstrate the effectiveness of the procedure.The developed procedure is feasible for screening and reviewing medications of a high number of older home care clients to identify clients with severe DRPs and provide interventions to solve them utilizing existing primary care resources.